IMPACT OF RAPID GROWING POPULATION ON THE INFRASTRUCTURE IN NIGERIA - Usman , Ibrahim (Multi-Disciplinary Research and Development Journals Int’l, 2025)
Nigeria’s rapid population growth—driven by high fertility and urban migration—places severe pressure on urban infrastructure. This chapter examines how expanding urban populations are reshaping housing, transport, healthcare, education, water and sanitation, and environmental systems in Nigerian cities. It synthesizes evidence on the scale and nature of the challenge, highlights human consequences (overcrowding, service shortages, informal settlement growth), and evaluates policy responses. The chapter closes with pragmatic strategies—planning and governance reforms, investments in affordable housing and public transport, water and sanitation scale-up, expanded health and education capacity, and family-planning and smart-city technologies—that can help align infrastructure provisioning with demographic realities.